System of Imaging Photometers for Upper Atmospheric Phenomena Study in the Arctic Region - Pavel Klimov; Sergei Sharakin; Alexander Belov; Boris Kozelov; Alexei Murashov; Roman Saraev; Daniil Trofimov; Alexei Roldugin; Vladimir Lubchich (Atmosphere, 2022)
A Pulsating Aurora Imaging Photometers Stereoscopic System (PAIPS) is suggested and described in the paper. The system is based on two lens telescopes with a matrix of multianode photomultiplier tubes as photodetectors placed in two high latitude observatories of the Polar Geophysical Institute. Telescopes provide simultaneous observations of a large volume of the atmosphere at altitudes in the range 50–100 km with high temporal resolution (up to 2.5 <semantics>μ</semantics>s) and a spatial resolution of about 2 km. This is a novel system for pulsating aurora study aimed to determine the energies of precipitating electrons responsible for the pulsating aurora occurrence. The system can be used for other atmospheric phenomena studies: meteors, transient luminous events, etc. One telescope has been operating since September 2021 and has measured a variety of optical phenomena.